The summer Hikaru died. 1 - Mokumokuren (Yen Press, 2023)
"It has Hikaru's face. It has Hikaru's voice. It even has Hikaru's memories. But whatever came down from the mountains six months ago isn't Yoshiki's best friend. Whatever it is, it's dangerous. Carrying on at school and hanging out as if nothing has changed--as if Hikaru isn't gone--would be crazy...but when it looks so very like Hikaru...and acts so very like Hikaru..."--Page 4 of cover.